The credit market handbook : (John Wiley & Son, 2006)
In The Credit Market Handbook, financial expert and Editor H. Gifford Fong has assembled a group of prominent professionals and academics familiar with the credit arena. In each chapter, a different expert analyzes a different issue related to today's dynamic credit market, including portfolio credit risk, valuation models, and the importance of modeling credit default.